Examining The Quarter-Life Crisis of Library Science Students at UIN Sunan Kalijaga Yogyakarta Through Digital Literacy Impact - Mutiara, Daliah; Laugu, Nurdin (Syarif Hidayatullah State Islamic University of Jakarta, 2024)
Rapid digital advancements present opportunities and challenges that significantly affect young adults' mental and emotional well-being. This study aims to 1) determine the level of digital literacy of UIN Sunan Kalijaga Library Science students, 2) determine the level of quarter-life crisis experienced by UIN Sunan Kalijaga Library Science students, and 3) determine the effect of digital literacy skills on quarter life crisis of UIN Sunan Kalijaga Library Science students. This research uses quantitative methods with descriptive and correlation types. The subjects are Library Science students’ classes of 2019 and 2020, and the object is the influence of digital literacy on the quarter-life crisis. Data collection was carried out using interview techniques, documentation, and questionnaires. Data were analyzed using mean, grand mean, product-moment correlation, and simple linear regression. The results of the analysis show that 1) students' digital literacy is in a very high category with a value of 3.4, 2) students experience a quarter-life crisis of 2.85 in the high category, and 3) digital literacy affects quarter-life crisis with a significance value of 0.000 <0.05. Based on the coefficient of determination, digital literacy affects 18.4% of quarter-life crises. Product moment correlation analysis shows a Pearson correlation value of -0.429, which means the higher the digital literacy, the lower the quarter-life crisis, and vice versa.